PRESERVASI ARSIP KONVENSIONAL DI ARSIP UNIVERSITAS GADJAH MADA - , VINIS DAYA M.ZEGA, Dra. Eny Kusmindarti W. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Preservation is a series of the life cycle in the archive management. There are three parts of the preservation namely, preventive, curative and reproduction. Preservation is also said a program of activities to perform maintenance and protection as well as extending the age of physical archives which is used to save information. This report deals with the technical implementation of preservation of the conventional static archives in Gadjah Mada University Archive. The methods to collect The Final Report data used observation, interviews, participated in the activities of preservation, and the literature studies. The discussion in this final project about the conventional archive preservation systems, infrastructure that is used, as well as the obstacles faced in the implementation of conventional archives preservation in Gadjah Mada University Archive. The conclusion of this Final Report that Gadjah Mada University Archive has a preservation system especially in conventional archives. Recently this institution has a problem to preparing the main material of preservation especially for restoration method is called tissue jepang. Until now that material is supported by National Archives of the Republic Indonesia (ANRI).